Penggunaan Aplikasi Canva Sebagai Upaya Presentasi Siswa SMP pada Matematika - Hanafi, Muhamad; Amalia, Annisa Fira Nindy; Khaillasiwi, Orbitha; Sari, Kumala; Muhsinin, Nurul; Karisma, Dita Wulan; Hadi, Muhamad Sofian (Media Pendidikan Matematika, 2023)
Using the Canva application is not just about installing pictures, but also how to make attractive presentations for students to present. Problems that are often faced by students in demonstrating the results of presentations are often less interesting. One of the things that can be done to simplify and create an attractive appearance in making a presentation material is to take advantage of a digital platform that provides various kinds of templates. An app that meets these criteria is Canva. Therefore, the purpose of this study is to describe the use of the Canva application as material for student presentations in demonstrating the results of discussions or group work in mathematics. The research method used is a literature study. This research resulted in the following conclusions: 1) efforts to improve junior high school students’ math presentation skills can be done with the Canva application; 2) there is a need for training in using Canva as a learning medium to improve junior high school students’ math presentation skills; 3) To find out other benefits and effectiveness in using the Canva application as a medium for learning mathematics, further research is needed to support the achievement and success in using media for learning mathematics.